Comparison of epistemological beliefs, teaching-learning conceptions, and self-efficacy of pre-service and in-service EFL teachers - Adnan Biçer; Şeyma Yıldırım (Journal of Pedagogical Research, 2023)
This study compares the epistemological beliefs, teaching-learning conceptions, and sense of self-efficacy of pre-service and in-service English as a Foreign Language (EFL) teachers with an aim to find probable statistically significant differences. Using a mixed-methods research design, the study collected quantitative data through two questionnaires and one scale, and the qualitative data through open-response questions. The participants were 374 pre-service teachers and 192 in-service teachers. 42 of the pre-service teachers and 19 of the in-service teachers volunteered to answer the open-response questions. Descriptive statistical techniques, t test, and content analysis were used to analyze the data. The findings show that both groups of teachers had relatively more sophisticated beliefs in learning process/expert knowledge and learning effort. Both groups adopted the constructivist conception more than the traditional conception, and they felt efficacious in instructional strategies, student engagement and classroom management respectively. Both groups had moderate levels of self-efficacy in classroom management, student engagement, and instructional strategies. However, the comparative analysis showed some significant differences. In-service teachers exhibited slightly stronger beliefs in innate-fixed ability and certainty knowledge. Pre-service teachers had slightly higher scores in the constructivist conception while in-service teachers had higher scores in the traditional conception. Furthermore, in-service teachers displayed slightly higher self-efficacy in classroom management and instructional strategies.